Índice de valor de importancia y diversidad en un bosque de colina baja en el distrito de Mazán, Loreto-Perú, 2024 - Pinedo Perez, Bruno Alexander (2025)
The study was carried out in forest concession No. 16-LOR-MAY/CON-MAD-2021 013 in the Mazan River basin. Trees were measured from 30 cm dbh in 46 sampling units of half a hectare with the aim of determining the importance value index and the diversity of a low hill forest. A total of 779 trees, 25 forest species, 23 genera and 12 botanical families were recorded. The families Fabaceae (196), Myristicaceae (177) and Lauraceae (100) present the largest number of trees. Nine species have the greatest ecological weight, being them: A. panurensis (28.2%), C. guianensis (24.3%), V. calophylla (22.0%) and O. parvifolia (21.0), V. albidiflora (17.1%), B. rubescens (15.7%), S. amara (14.8%), C. estrellensis (13.9%) and H. oblongifolia (13.3%). The low hill forest has a medium diversity (Shannon: 3.06; Simpson: 0.94; Margalef: 3.605). Enrichment with O. platyspermum, D. micrantha, M. bidentata is recommended due to their low importance value index in order to increase the economic benefit of the low hill forest. Likewise, reforestation plans should be implemented with A. panurensis, C. guianensis, and V. calophyllaque, as they have high values on the importance value index.